9a + 7b *remember to look and understand the letters!*
It is equivalent to 53a+44b when simplified
The solution for the value of 3a would be -3. The equation would be 6a + 3(4) = 2.
9a = 6a + 4 subtracting 6a from each side, 3a = 4 dividing each side by 3, a = 4/3
Add them together: 3a+4a-a = 6a
Collect the terms in a, then the terms in b, getting 6a - 3a + 2b + 5b which simplifies to 3a + 7b. Gettit?
It is an algabraic expession without knowing whether or not 2b and 3a are plus or minus
It is 6a + 4
it is 6a
4y - 4 + 3a + 7 - 6a - 4 = 4y -1 - 3a
Area: 15ab Perimeter: 2(3a+5b) or as 6a+10b
2a² + 6a
3a + 4b - (-6a) - 3b? There is no equivalent because you did not make it an equality. However you could combine the numbers... 3a + 4b +6a -3b = 9a + 1b
4(5b - 6a^2)(5b + 6a^2)